DESIGN EVALUATION OF WINDOW DESIGN TO DAYLIGHT EFFICACY IN IBU DAN ANAK MELINDA HOSPITAL’S INPATIENT ROOM, BANDUNG - Syarifah (Jurnal Riset Arsitektur, 2019)
Abstract- Daylight performance in patient room is very important. Which in this research, daylight performance is measured by its distribution, daylight factor and glare precaution. Those elements are calculated according to lighting standard for the hospital building and how the performance adapt to patient's visual comfort. Therefore window design is needed to be considered as its affected to daylight performance inside the room. The object observation shows a result of the contradiction between each combination of window design and room plan. This research evaluates how window design affects the performance of natural lighting and analyze which window design suitable for each room plans, and also the alternative design that will be more suitable for some rooms’ plan and condition. This research is conducted by explanatory method, with quantitative and qualitative approach. Velux visualizer software is used to simulate how natural light is distributed to the inpatient room. Obtained data shows that natural lighting performance in RSIA Melinda inpatient room is still below the determined standard. And noticed that room orientation, window position and dimension, exterior exsiting conditions are factors that affected the daylight performance. The design recommendations are sun shading and glazing material.  Design recommendations are given to the majority room type and also in consideration of the design applicable possibility. Key Words: window design, daylight, inpatient room, spatial arrangement